Post-COVID-19 vaccination occurrence of splenic infarction due to arterial thrombosis. Issue 12 (7th December 2021) - Anderson, Alexander; Seddon, Mary; Shahzad, Khalid; Lunevicius, Raimundas
Abstract : We present the case of an 82-year-old woman admitted to a regional emergency general surgery centre with severe left upper quadrant abdominal pain and tenderness within 21 days of receiving the first dose of the ChAdOx1 nCov-19 vaccine (Vaxzevria, AstraZeneca). Following further investigation through CT imaging, a thrombus was discovered in the patient's splenic artery resulting in a large splenic infarct. Splenic infarcts are rare and it is important to note the association between time of administration of the first dose of vaccine and the occurrence of thromboembolic complications in the noted absence of other risk factors for this condition. We hypothesise a link between Vaxzevria vaccine injection and a rare form of thromboembolic complication: thrombosis of the splenic artery.